2017
DOI: 10.7567/jjap.56.022301
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of monocrystalline silicon solar cells with fine nanoimprinted textured surface

Abstract: We investigated the surface reflectance of nanoimprinted textures on silicon. Zirconium oxide, which is a wide-bandgap inorganic dielectric material, was used as the texturing material. We performed several calculations to optimize the textures for the production of high-efficiency bulk-type monocrystalline silicon solar cells. Our analysis revealed that nanoimprinted textured solar cells exhibit a lower reverse saturation current density than a solar cell with a conventional etched texture. It was also confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The surface reflectance shown in figure 10 shows a high value remains in the short wavelength region. The height of the ZnO moth-eye structure, which strongly influences the surface reflectance in the short wavelength region, should be as high as 200 nm according to [25] while this report has it around 100 nm. In addition, the refractive index of ZnO usually reaches 1.9 at the 790 nm wavelength while this report found that the moth-eye part was only 1.64 at the 605 nm wavelength and 1.62 at the 790 nm wavelength.…”
Section: Zno Moth-eye Structure With Si-rich Sin For Lower Surface Re...mentioning
confidence: 77%
See 1 more Smart Citation
“…The surface reflectance shown in figure 10 shows a high value remains in the short wavelength region. The height of the ZnO moth-eye structure, which strongly influences the surface reflectance in the short wavelength region, should be as high as 200 nm according to [25] while this report has it around 100 nm. In addition, the refractive index of ZnO usually reaches 1.9 at the 790 nm wavelength while this report found that the moth-eye part was only 1.64 at the 605 nm wavelength and 1.62 at the 790 nm wavelength.…”
Section: Zno Moth-eye Structure With Si-rich Sin For Lower Surface Re...mentioning
confidence: 77%
“…The difference of the refractive index at the interface has to be minimized to suppress the surface reflection. In this study, we proposed the layer insertion to reduce such reflection between ZnO and c-Si, as shown in the above section, and the refractive index of the inserted layer should be around 3 according to [25]. In addition, the utilized Si-rich SiN should be around 40 nm in thickness.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Due to a dramatic increase of devices with display screens and the wide adoption of solar panels, the demand for an antireflection structure is increasing. [1][2][3][4] A general anti-reflection structure is a multilayer film, which is both time and cost intensive to produce. In addition, there is a limit to the wavelength and incident angle at which reflection can be suppressed.…”
Section: Introductionmentioning
confidence: 99%